Paideia: humanistično pedagoško bistvo paideia in njegovo uresničevanje v vzgojnoizobraževalni praksi antičnih Grkov - Autor, Oskar (University of Maribor Press, 2003)
Paideia: the humanistic pedagogical essence of paideia and its implementation in the educational practice of the ancient Greeks. No abstract.